The DPP4 Inhibitor Linagliptin Protects from Experimental Diabetic Retinopathy - Dietrich, Nadine; Kolibabka, Matthias; Busch, Stephanie; Bugert, Petra; Kaiser, Ulrike; Lin, Jihong; Fleming, Thomas; Morcos, Michael; Klein, Thomas; Schlotterer, Andrea; Hammes, Hans-Peter (PLOS ONE, 2016)
Background/aims Dipeptidyl peptidase 4 (DPP4) inhibitors improve glycemic control in type 2 diabetes, however, their influence on the retinal neurovascular unit remains unclear. Methods Vasculo- and neuroprotective effects were assessed in experimental diabetic retinopathy and high glucose-cultivated C. elegans, respectively. In STZ-diabetic Wistar rats (diabetes duration of 24 weeks), DPP4 activity (fluorometric assay), GLP-1 (ELISA), methylglyoxal (LC-MS/MS), acellular capillaries and pericytes (quantitative retinal morphometry), SDF-1a and heme oxygenase-1 (ELISA), HMGB-1, Iba1 and Thy1.1 (immunohistochemistry), nuclei in the ganglion cell layer, GFAP (western blot), and IL-1beta, Icam1, Cxcr4, catalase and beta-actin (quantitative RT-PCR) were determined. In C. elegans, neuronal function was determined using worm tracking software. Results Linagliptin decreased DPP4 activity by 77% and resulted in an 11.5-fold increase in active GLP-1. Blood glucose and HbA1c were reduced by 13% and 14% and retinal methylglyoxal by 66%. The increase in acellular capillaries was diminished by 70% and linagliptin prevented the loss of pericytes and retinal ganglion cells. The rise in Iba-1 positive microglia was reduced by 73% with linagliptin. In addition, the increase in retinal Il1b expression was decreased by 65%. As a functional correlate, impairment of motility (body bending frequency) was significantly prevented in C. elegans. Conclusion Our data suggest that linagliptin has a protective effect on the microvasculature of the diabetic retina, most likely due to a combination of neuroprotective and antioxidative effects of linagliptin on the neurovascular unit.